The effect of the ethanolic extract of African leaves (Vernonia amygdalina Delile) on the corrosion rate and microstructure of stainless steel orthodontic wire - Siti Bahirrah; Syafruddin Ilyas; Ida Bagus Narmada; Ameta Primasari; Widya Lestari; Indra; Ervina Sofyanti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Stainless steel orthodontic wire is commonly used in orthodontic treatment but is prone to corrosion; therefore, an inhibitor is required. Purpose: This study aimed to evaluate the effectiveness of the ethanolic extract of African leaves (Vernonia amygdalina Delile) as a corrosion inhibitor for stainless steel wires. Methods: A laboratory experiment with a pre- and post-test control group design was conducted. Samples included one negative control (artificial saliva), one positive control (chlorhexidine), and two treatment groups (ethanolic extract of African leaves at 3.125 mg/mL and 6.25 mg/mL), totaling 28 samples. Immersion lasted 7 days at 37°C. Corrosion rates were measured by weight loss, and microstructural changes were analyzed using a scanning electron microscope. Results: The highest average corrosion rate was observed in the chlorhexidine group (0.98 ± 0.58 mils per year [mpy]), whereas the lowest was in the 6.25 mg/mL extract group (−0.04 ± 0.80 mpy). Scanning electron microscope analysis revealed notable microstructural differences: the artificial saliva group showed long scratches scattered across the surface and localized round porosity; the chlorhexidine group exhibited rough scratches and widespread porosity; in contrast, the African leaves groups displayed minor scratches and a thin layer presumed to be protective. Conclusion: The ethanolic extract of African leaves considerably affects corrosion rates and microstructural changes in stainless steel orthodontic wires.